'Twilight of the idols' and Nietzsche's late philosophy: Toward a revaluation of values - Brobjer, Thomas H. (New York, USA: Bloomsbury Academic, 2023)
"Connects Nietzsche's Twilight of the Idols to his revaluation of all values project, creating a new perspective on his late philosophy"--
Keywords: Philosopher; Nieizsche, Fredrich